Design Thinking & Virtual Management Training: A Systematic Literature Review (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Does the time of 21st century training  necessitate exploration into emerging research  pedagogies like design thinking for a better  understanding of how design influences  business and management? This review  explains the changes in training perspectives  within management settings using creative  engagement methods like design thinking  which call into question the future of dynamic  business innovation. The paper undertakes a  Systematic Literature Review of this nascent  field, followed by a Bibliometric Analysis,  Content Analysis to present a taxonomy of the  field, and finally outlines interesting questions  for future research to address.
Keywords: Design Thinking; Virtual; Management Training; Systematic Literature Review